PENGGUNAAN JUS KULIT BUAH NAGA UNTUK MENGATASI NYERI SAAT MENSTRUASI (DISMENOREA): DRAGON FRUIT SKIN FOR OVERCOME PAIN WHEN MENSTRUATION (DISMENOREA) (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2019)
ABSTRACTMenstrual pain, or medical dysmenorrhea, is pain in the lower abdomen during menstruation and can also be felt on the hips, lower back, or thighs. The pain is convulsive (convulsions), which are felt by some women at the beginning of menstruation. Dysmenorrhoea can also be overcome non-pharmacologically, which can naturally reduce the intensity of the pain. This research is an experimental analytical research that is a research on the level of naturalness (setting) where research is in addition to survey research and naturalistic (qualitative). Essentially, experimental research is to examine the effect of the treatment on the behavior that results from the treatment. This study was conducted to determine the intensity of menstrual pain after eating dragon fruit skin juice. The first 3 months focused on reducing the intensity of pain after eating dragon fruit skin juice with a composition of 100 grams of dragon fruit skin mixed with sugar and enough water. The second 3 months focused on reducing the intensity of pain after eating dragon fruit skin juice with a composition of 200 grams of dragon fruit skin mixed with sugar and sufficient water. The third 3 months focused on reducing the intensity of pain after eating dragon fruit skin juice with a composition of 100 grams of dragon fruit skin mixed with milk and sufficient water. In addition, the study also received information on how to reduce the intensity of menstrual pain by applying non-pharmacological techniques by using dragon fruit